2017
DOI: 10.1155/2017/4209257
|View full text |Cite
|
Sign up to set email alerts
|

Association of GCLM -588C/T and GCLC -129T/C Promoter Polymorphisms of Genes Coding the Subunits of Glutamate Cysteine Ligase with Ischemic Heart Disease Development in Kazakhstan Population

Abstract: Background Glutamate cysteine ligase (GCL) is a rate-limiting enzyme in synthesis of glutathione. Evidence suggests that genetic variations in the promoter region of genes coding a catalytic subunit (GCLC -129T/C) and a modifier subunit (GCLM -588C/T) of GCL have a functional impact on their transcriptional activity and were associated with various disorders. Hence, we hypothesize whether these two polymorphic variants of GCLM and GCLC genes are associated with the risk of ischemic heart disease (IHD) developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…GCLC is a subunit of the first rate-limiting enzyme of glutathione synthesis. Promoter polymorphisms of GCLC have been associated with increased risk of ischemic heart disease in the Kazakhstani population [26]. Uthus and Ross showed that the expression of GCLC was upregulated by selenium deprivation in both rat and mouse liver [27], while increased levels of glutamate-cysteine ligase ( GCL ) may drive glutathione ( GSH ) synthesis in response to oxidants, providing a protective mechanism against oxidative stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…GCLC is a subunit of the first rate-limiting enzyme of glutathione synthesis. Promoter polymorphisms of GCLC have been associated with increased risk of ischemic heart disease in the Kazakhstani population [26]. Uthus and Ross showed that the expression of GCLC was upregulated by selenium deprivation in both rat and mouse liver [27], while increased levels of glutamate-cysteine ligase ( GCL ) may drive glutathione ( GSH ) synthesis in response to oxidants, providing a protective mechanism against oxidative stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the disease relevance of polymorphisms in genes involved in glutathione biosynthesis, notably glutathione cysteine ligase (GCL) and glutathione synthetase (GS), which directly affect cellular GSH concentrations [ 29 ]. Polymorphisms in the catalytic subunit of GCL ( GCLC ) have been associated with cystic fibrosis [ 30 ], chronic obstructive pulmonary disease [ 31 ], pulmonary tuberculosis [ 32 ], drug sensitivity in human tumor cell lines [ 33 ], methylmercury retention [ 34 ], vasomotor function and myocardial infarction [ 35 , 36 ]. Functional polymorphisms in the GCL modifier subunit ( GCLM ) have been linked with ischemic heart disease and vasomotor function [ 36 , 37 ], and in some cases, schizophrenia [ [38] , [39] , [40] ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the catalytic subunit of GCL ( GCLC ) have been associated with cystic fibrosis [ 30 ], chronic obstructive pulmonary disease [ 31 ], pulmonary tuberculosis [ 32 ], drug sensitivity in human tumor cell lines [ 33 ], methylmercury retention [ 34 ], vasomotor function and myocardial infarction [ 35 , 36 ]. Functional polymorphisms in the GCL modifier subunit ( GCLM ) have been linked with ischemic heart disease and vasomotor function [ 36 , 37 ], and in some cases, schizophrenia [ [38] , [39] , [40] ]. Lastly, polymorphisms in GS have been associated with susceptibility to lung dysfunction and lung cancer, as well as patient survival [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most commonly investigated promoter polymorphisms of the GCLC and GCLM genes are GCLC rs17883901 (c.-129C>T) and GCLM rs41303970 (c.-590 C>T). 17 , 18 , 19 , 20 Some studies indicated that polymorphisms in GCLC and GCLM genes are associated with low levels of reduced GSH in vitro , which may explain susceptibility to certain diseases related to oxidative stress. 17 , 18 The GCLC rs17883901 polymorphism has been suggested to suppress the GCLC gene induction response to oxidants and it has been implicated in coronary endothelial dysfunction and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“… 21 The presence of GCLC rs17883901 T allele and GCLM rs41303970 T allele has also been associated with an increased risk of ischemic heart disease. 19 However, according to the available literature the association between GCLC and GCLM polymorphisms and asbestos-related diseases has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%